Pola Asuh Orang Tua Nelayan Pesisir Lamongan dalam Pembinaan Akhlak Anak - Kusuma Ningtias, Ratih; Karomah, Wardatul; Eko Saputro, Danang (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
This study aims to describe the parenting style of fishermen's parents in fostering children's morals in Kranji village, Paciran sub-district, Lamongan district.This research uses a qualitative descriptive approach with a case study type of research. The results of this study indicate that: (1) The views of fishermen's parents in Kranji village on parenting patterns in fostering children's morals. they see that the parenting style of parents especially in fostering morals is very important and necessary. parents have an obligation to educate, guide, control their children so that in the future they will become pious children. (2) Implementation of the parenting style of fishermen parents in Kranji village towards their children in fostering morals which includes: (a) The way parents in fostering children's morals by teaching kindness, generosity, courtesy, obedience to parents, setting a good example. (b) The parents' way of reminding them to pray and recite the Koran is by ordering them to pray at the mosque ect. Parents are still lacking in giving examples (c) The way parents monitor children's activities outside with permits, checking cellphones, time limits, asking friends who they play with. (d) the way parents monitor their children's learning at home and at school, namely by leaving their children in less places, is not monitored at all. (3) There are three models of parenting parents of fishermen in Kranji village in fostering morals, namely authoritarian parenting, democratic parenting, and permissive parenting. (4) The parents of the fishermen in Kranji village give rewards by giving praise, motivating their children so that their children are even more enthusiastic about doing good and achieving.